Pengaruh model discovery berbantuan media audio visual terhadap kemampuan berpikir kritis ditinjau dari minat belajar siswa - Fahmi, Nur; Soekamto, Hadi; Deffinika, Ifan (Universitas Negeri Malang, 2023)
One of the skills that need to be possessed by students as the 2013 curriculum demands in the 21st century is critical thinking skills. The purpose of this research is (1) to determine the effect of the discovery model assisted by audio-visual media on critical thinking skills in geography subjects (2) in order to determine the effect of the discovery model assisted by audio-visual media on critical thinking skills in terms of student learning interest. This type of research is a quasi-experimental research design with posttest only control group design. The subjects used in this study were class XI IPS 2 as the experimental class and XI IPS 1 as the control class. Students' critical thinking ability is measured using an essay test that leads to indicators of critical thinking ability. The moderator variable in this study is students' interest in learning which is measured using a questionnaire instrument. The hypothesis in this study uses an independent sample t-test and two-way ANOVA assisted by IBM SPSS Statistics 25. From the results of the independent sample t-test test, it gives significant results, namely 0.000 less than 0.05. This value indicates an effect of discovery model assisted by audio-visual media on critical thinking skills. While the two-way ANOVA test results show a significant level of 0.032 less than 0.05, it can be concluded that there is an effect of discovery model assisted by audio-visual media on critical thinking skills in terms of student interest in geography subjects at SMA Negeri 2 Lambu. Salah satu keterampilan yang perlu dimiliki oleh siswa sebagai tuntutan kurikulum 2013 pada abad 21 adalah keterampilan berpikir kritis. Adapun tujuan dilakukan penelitian ini adalah (1) untuk mengetahui pengaruh dari model discovery berbantuan media audio visual terhadap kemampuan berpikir kritis pada mata pelajaran geografi (2) agar dapat mengetahui pengaruh model discovery berbantuan media audio visual terhadap kemampuan berpikir kritis ditinjau dari minat belajar siswa. Jenis penelitian ini adalah eksperimen semu dengan desain penelitian posttest only control group design. Subjek yang digunakan pada penelitian ini adalah kelas XI IPS 2 sebagai kelas eksperimen dan XI IPS 1 sebagai kelas kontrol. Kemampuan berpikir kritis siswa diukur menggunakan tes essay yang mengarah pada indikator kemampuan berpikir kritis. Variabel moderator pada penelitian ini yaitu minat belajar siswa yang diukur menggunakan instrumen angket. Hipotesis pada penelitian ini menggunakan uji independent sample t-test dan two way anova berbantuan IBM SPSS Statistics 25. Dari hasil uji independent sample t-test memberikan hasil yang signifikan yaitu 0.000 kurang dari 0.05. Nilai tersebut menunjukkan bahwa terdapat pengaruh model discovery berbantuan media audio visual terhadap kemampuan berpikir kritis. Sedangkan hasil dari uji two way anova menunjukkan taraf nilai signifikan sebesar 0.032 kurang dari 0.05, maka dapat diambil kesimpulan bahwa ada pengaruh model discovery berbantuan media audio visual terhadap kemampuan berpikir kritis ditinjau dari minat belajar siswa pada mata pelajaran geografi SMA Negeri 2 Lambu.